The Hearing Threshold of Employees Exposed to Noise Generated by the Low-Frequency Ultrasonic Welding Devices - DUDAREWICZ, Adam; ZABOROWSKI, Kamil; RUTKOWSKA-KACZMAREK, Paulina; ZAMOJSKA-DANISZEWSKA, Małgorzata; ŚLIWIŃSKA-KOWALSKA, Mariola; ZAMYSŁOWSKA-SZMYTKE, Ewa; PAWLACZYK-ŁUSZCZYŃSKA, Małgorzata (Archives of Acoustics, 2017)
The aim of the study was to assess the hearing threshold levels (HTLs) in employees exposed to noise generated by low-frequency ultrasonic technological equipment in comparison with the HTLs of workers exposed to audible noise at the similar A-weighted equivalent-continuous sound pressure level. The study includes measurements of ultrasonic and audible noise at workplaces and hearing tests, i.e. conventional pure-tone audiometry and extended high-frequency audiometry. The study group comprised 90 workers, aged 41.4±10.0 years (mean±SD), exposed for 17.3±9.8 years to noise generated by ultrasonic devices at mean daily noise exposure level () of 80.6±2.9 dB. The reference group consists of 156 subjects, exposed to industrial noise (without ultrasonic components) at similar A-weighted equivalent-continuous sound pressure level ( = 81.8±2.7 dB), adjusted according to age (39.8±7.7 years), gender and job seniority (14.0±7.0 years). This group was selected from database collected in the Nofer Institute of Occupational Medicine. Audiometric hearing threshold levels in the frequency range of 0.5–6 kHz were similar in both groups, but in the frequency range of 8–12.5 kHz they were higher in the group of employees exposed to ultrasonic noise. The findings suggest that differences in the hearing threshold (at high frequencies) in analyzed groups may be due to differences in spectral composition of noise and show the need to continue the undertaken studies.